On Determining the Concept of “Disciplinary Liability of Police Officers” - D. Ye. Zherebtsov (Law and Safety)
The essence of legal liability in labor law has been clarified. Scientific approaches to the definition of “disciplinary liability” have been studied. The purpose of disciplinary liability of employees has been defined. The author has studied the norms of the Law of Ukraine “On the Disciplinary Statute of the National Police of Ukraine” regarding the procedure for applying disciplinary liability to police officers.